NUMERICAL SIMULATION ON STRESS CORROSION CRACK GROWTH RATE OF 316L STAINLESS STEEL IN DISSOLVED OXYGEN ENVIRONMENT BASED ON A COUPLED DIFFUSION-COHESION MODEL (Jixie qiangdu)
Dissolved oxygen is one of the main environmental parameter affecting of stress corrosion cracking of austenitic stainless steel in high temperature water environment.Based on the slip-dissolution of stress corrosion theory,a coupled diffusion and cohesion model was built for simulating stress corrosion crack.The stress corrosion cracking behavior of 316L austenitic stainless steel in high temperature water of 325℃ with dissolved oxygen was simulated by finite element analysis using cohesive element.The effects of dissolved oxygen content and cold working on crack growth rate(CGR)were analyzed.The results indicate that,by appropriately calibrating the model parameters,the built model can predict the CGR of stress corrosion cracking under different dissolved oxygen contents,showing that the calculated CGR agrees well with the experimental results reported in the literature.Furthermore,the relationship between the stress corrosion crack growth rate and the yield strength of 316L stainless steel can be fitted as CGR∝σy2.028 in the simulated high temperature water and stress intensity factor conditions.